2021
DOI: 10.1155/2021/6697697
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Human Posture Recognition and Estimation Method Based on 3D Multiview Basketball Sports Dataset

Abstract: In traditional 3D reconstruction methods, using a single view to predict the 3D structure of an object is a very difficult task. This research mainly discusses human pose recognition and estimation based on 3D multiview basketball sports dataset. The convolutional neural network framework used in this research is VGG11, and the basketball dataset Image Net is used for pretraining. This research uses some modules of the VGG11 network. For different feature fusion methods, different modules of the VGG11 network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Regarding the used data for the development and testing of the systems, on the one hand, several papers such as [ 12 , 13 , 14 , 15 , 17 , 18 , 20 , 37 , 38 , 42 ], developed their own datasets using manual annotations, MoCap systems, or other ground truth generation methods, but did not make them publicly available. Other papers created and published their dataset to contribute to the research community, such as [ 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the used data for the development and testing of the systems, on the one hand, several papers such as [ 12 , 13 , 14 , 15 , 17 , 18 , 20 , 37 , 38 , 42 ], developed their own datasets using manual annotations, MoCap systems, or other ground truth generation methods, but did not make them publicly available. Other papers created and published their dataset to contribute to the research community, such as [ 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches are trying to solve specific estimation problems in different environments, such as the ones for basketball [ 14 ], diving [ 24 ], hockey [ 35 ], etc, while others try to create a general sports use system, such as [ 39 , 41 ]. Taking into account the limited amount of work in specific sports, we can say that interesting research and development can be found regarding HPE and hockey .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After four downsamplings, the resolution is only 1/16 of the original, that is, 32 * 32. Although advanced features are extracted from the network, a large amount of low-level feature information is discarded, which makes the image blurred and difficult to recover in upsampling [14].…”
Section: Improvement Of Decodermentioning
confidence: 99%